Restorative potential of ciliary body cells in a retinal ganglion cell degeneration model - Fernando Lucas-Ruiz; Marta Fernández-Nogales; Francisco J. Valiente-Soriano; Macarena Herrera; Francisco M. Nadal-Nicolás; Marta Agudo-Barriuso; Eloisa Herrera (Scientific Reports)
Abstract The ciliary body (CB) has been proposed as a niche of neural stem cells because, in vitro, cells from this area are able to form neurospheres, proliferate and differentiate. Here, we explore the potential of CB cells to differentiate and replace degenerated retinal ganglion cells (RGCs) in vivo. CB cells and cells from the subventricular zone (SVZ) were isolated from adult or postnatal C57BL/6Tg(CAG-EGFP) mice, respectively, and intravitreally injected into intact retinas, immediately after optic nerve crush or 45 days after the lesion of adult C57/BL/6 mice. Retinas were analysed in whole mounts or cross sections at different time points. Controls were matched untreated retinas. Neither cell type caused gliosis or toxicity when injected into intact retinas. When CB or SVZ cells were injected right after axotomy, they formed an epimembrane without integrating in the retina. However, when CB cells were administered in retinas depleted of RGCs, they integrated into the ganglion cell layer and expressed RGC and neuronal markers. Although SVZ cells were also able to integrate into RGC depleted retinas they did so more slowly than CB cells. These results shed light in the long-standing question of whether cells in the CB have the potential to transdifferentiate in vivo and point to the CB as a suitable source of cells that could be used in cell-replacement therapies for neurodegenerative diseases of the retina.